Experimental Investigations Concerning the Sensitivity of the Leakproofness Test for Dangerous Goods Packagings Relating to the Leak Diameter. (14th June 2013) - Schlick‐Hasper, Eva; Jahnke, Wolfgang; Drousch, Björn; Goedecke, Thomas; Kraume, Matthias
<x xml:space="preserve">Abstract</x> The objective of this experiment was to verify that in regards to the leakproofness bubble test for packagings of dangerous goods, a reduction of the air overpressure from 0.2 to 0.1 bar can be compensated for by reducing the water surface tension to a value of approximately 33.2 mN/m by adding a wetting agent. It was experimentally proven that this method will yield the same leak diameters. This is important to avoid irreversible deformations during the leaktesting of intermediate bulk containers (IBCs) while using a test overpressure of 0.2 bar. Bubble test experiments were carried out on artificial borehole‐shaped leaks manufactured of two different materials high density polyethylene (HDPE) and stainless steel by ultrashort pulse laser technology and with two different immersion test liquids (deionized water and a 0.1% Lutensol FSA fabric softener active 10 solution). The characteristic diameters of the boreholes investigated were from 11.5 to 30.3 µm in length. Copyright © 2013 John Wiley & Sons, Ltd.